PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS ICT (INFORMATION,COMMUNICATION, AND TECHNOLOGY) TERHADAP MOTIVASI BELAJAR SISWAKELAS X PADA PEMBELAJARAN EKONOMI DI SMAN 1 BANGUNTAPAN - Miftakhul Hidayah, Sri Nuryanto, dan Miftahul Fawaid (Pelita - Jurnal Penelitian Mahasiswa UNY, 2010)
This research aimed to discover how much influence the use of ICT‐based Learning Media onstudent motivation in learning economics class X in SMA N 1 Banguntapan. The research methodused in this study is the experimental method.While the research design that was used is "control‐group pretest‐posttest design." Then thedata collection techniques used in this study were divided into 3 stages: the first is the pre ‐ test(initial data collection ability students), the second is the final test post test to determine studentachievement, and the third is through the Student Activity Evaluation Sheet show indications of a lackof student motivation to economic subjects.The results related to the influence of the implementation of ICT‐based instructional mediaon student motivation shows the value and impact of a positive nature, which in the execution of thisstudy indicate that the economic conditions of the learning experience rapid progress. Learningmedia are made with a very attractive design combined with sound effects, video, photo, andelements ‐ elements of other instructional media support, so that it becomes a strategy that canenhance students' motivation in the classroom. The ‐ average value obtained by the students duringthe pre ‐ test before the use of ICT‐based instructional media on economic subjects is at 7 and theaverage value of students as post‐test after the use of ICT‐based instructional media is at 8.5. Sofrom these results it can be concluded, that there is increasing student motivation to economicsubjects after the use of ICT learning media that can be seen from an increase in student learningoutcomes.Keywords: ICT‐based Learning Media, motivation to learn, Economics